Meningkatkan kemampuan menyajikan data dalam diagram batang melalui penerapan model pembelajaran problem based learning (PBL) di sekolah dasar - Suprihatin, Retno (Universitas Sebelas Maret, 2021)
Abstract. This article contains the result of research conducted on fourth grade elementary school students. As for the background of this research is the low ability of fourth grade students in presenting data on bar charts. The low ability of students in this material is influenced by: (1) students’ ability to solve problems is still low, (2) students often make mistakes in placing the components on bar chart, (3) students are not careful in reading data, and (4) distance learning by giving lots of practice questions makes students confusion. Efforts to improve the ability to present data on bar charts carried out in this study were to apply the problem based learning, especially about presenting data in bar charts. This research is a classroom action research. The results of this study indicate an increase in the value of the evaluation results carried out at the end of each cycle. This increase in learning outcomes proves that the problem based learning model is able to improve students’ ability to present data on bar charts.